Pemanfaatan Kecerdasan Buatan dibidang Kesehatan Lingkungan dalam Upaya Mencapai Tujuan Pembangunan yang Berkelanjutan: Utilisation of Artificial Intelligence in Environmental Health to Achieve Sustainable Development Goals - Martias, Indra; Daswito, Rinaldi (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2024)
The utilization of artificial intelligence (AI) in the field of environmental health is one of the important innovations for achieving sustainable development goals (SDGs).  AI has enormous potential in monitoring air quality, managing waste, and mitigating environmental disasters such as forest fires and water pollution. However, the application of this technology in Indonesia still faces various challenges, including limited digital infrastructure, a lack of standardized environmental data, a lack of experts, and an inadequate regulatory framework. These barriers hinder the full potential of AI in supporting more effective and efficient environmental management. Synergies between the government, academia, the private sector, and society are necessary to overcome these challenges and create an ecosystem conducive to AI development. We must take strategic steps that support technological innovation, increase investment in digital infrastructure, and build human resource capacity. With this collaborative approach, AI can play a significant role in strengthening efforts to maintain environmental health, improve people's quality of life, and accelerate the achievement of sustainable development goals in Indonesia. This article provides a comprehensive insight into the potential, challenges, and solutions of AI implementation in environmental health as part of a sustainable development strategy.